(untitled) (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2024)
Legal politics concerns the issue of legal renewal - to understand the direction of legal politics trying to make rules that will determine how to understand the direction of human action. Legal development in Indonesia must first understand the politics of national law adopted in Indonesia. humans act. investigate what changes must be made in the law that is currently in effect in order to be in accordance with social werkelijkheid (social reality). Basically, labor issues are a social, political, and economic agenda that are quite crucial in modern countries, because actual employment issues are not only the relationship between workers and employers, but more broadly also include issues of the economic system of a country and at the same time the social system. the politics. Therefore, the economy and politics of a country will greatly determine the pattern and color